A GIS Based Integration Method for Geothermal Resources Exploration and Site Selection. Issue 2 (April 2015) - Noorollahi, Younes; Ghasempour, Roghayeh; Jalilinasrabady, Saeid
A toolbox using a Geographic Information System (GIS) was developed and introduced as a decision-making tool to locate potential geothermal areas. The study aims to introduce step-by-step guidelines and develop a user friendly computer program that can determine promising geothermal areas. Six data layers characterizing the geothermal area are employed in the site selection process. ArcMap was used as a base program to develop the GIS Model for Geothermal Resource Exploration (GM-GRE), which consists of geoprocessing tools and a model builder. Criteria for defining promising areas based on each layer are defined using spatial relationship analysis of currently producing geothermal wells in Akita and Iwate prefectures in northern Japan as proven geothermal resources and evidence layers. Areas with geothermal potential were defined and prioritized using input data layers.